A eficácia do treinamento de habilidades com cadeiras de rodas manuais no desempenho ocupacional e engajamento de sujeitos com lesão medular - Caro, Camila Caminha (2019)
Introduction: Evidences indicate the efficacy of wheelchair skills training in participants with spinal cord injury in the use of the resource. However, its efficacy in the occupational performance and engagement of individuals with spinal cord injury is still unknown. Objectives: To assess the efficacy of wheelchair skills training in the occupational performance and engagement of individuals with spinal cord injury. Methods: We conducted a longitudinal prospective intervention study; it is a self-control clinical trial with mixed methods. We used a non-probability convenience sampling of 11 participants with spinal cord injury from a mid-sized city in the state of São Paulo. The intervention was performed in the participants’ community by an occupational therapist over an average period of 8 hours per participant. Only 7 out of the 11 of the therapists were formalized. For the initial evaluation (IE), we employed the following measures: (1) An Identification Form of the participant with spinal cord injury; (2) The Functional Independence Measure; (3) The Canadian Occupational Performance Measure; (4) The Wheelchair Skills Test - Questionnaire; (5) The Functional Mobility Assessment, and (6) The Quebec User Evaluation of Satisfaction with Assistive Technology 2.0. After the intervention, we conducted the Revaluation 1 (R1) and applied the measures (2), (3), (4), (5), and (6). After 1 month, Revaluation 2 (R2) was performed with the application of the same measures, with the addition of a semi-structured interview to assess the participants’ opinion of the training they received. The data went through simple, descriptive analysis, and also through the Friedman non-parametric test, the Conover multiple comparisons test, and content analysis. Results: We observed statistically significant differences, at a rate of 5%, between the IE and the R1 analyzes. The differences were observed in the functional independence, in the capacity, confidence and frequency of wheelchair use, and the participants’ satisfaction with the use of a wheelchair in their daily life. The results remained unaltered through the R2, except for the wheelchair skills performance. Furthermore, we observed qualitative reports of subjective experience, an active involvement in the occupation, and social and environmental interaction. Conclusion: Our results demonstrate the efficacy of the wheelchair skills training in the occupational performance and engagement of the participants with spinal cord injury. The findings point to the importance of such practices in community-oriented public services.